Think Before You Act: Improving the Conservation Outcomes of CITES Listing Decisions - Cooney, Rosie; Challender, Daniel W. S.; Broad, Steven; Roe, Dilys; Natusch, Daniel J. D. (Frontiers in Ecology and Evolution, 2021)
The CITES treaty is the major international instrument designed to safeguard wild plants and animals from overexploitation by international trade. CITES is now approaching 50 years old, and we contend that it is showing its age. In stark contrast to most environmental policy arenas, CITES does not require, encourage, or even allow for, consideration of the impacts of its key decisions—those around listing species in the CITES Appendices. Decisions to list species in CITES are based on a simplistic set of biological and trade criteria that do not relate to the impact of the decision, and have little systematic evidentiary support. We explain the conservation failures that flow from this weakness and propose three key changes to the CITES listing process: (1) development of a formal mechanism for consideration by Parties of the likely consequences of species listing decisions; (2) broadening of the range of criteria used to make listing decisions; and (3) amplification of the input of local communities living alongside wildlife in the listing process. Embracing these changes will help to ensure CITES decisions more effectively respond to the needs of wildlife in today’s highly complex and dynamic conservation context.